Unhomely Home: Cultural Encounter of Diaspora in Jhumpa Lahiri’s The Namesake - Paudel, Rudra Prasad (NUTA Journal, 2019)
This article discusses unhomely home of the diasporas which is constructed geographically and psychologically by encountering the alien culture based on Jhumpa Lahiri’s novel The Namesake. The purpose was to highlights recent debate on ‘home’ for immigrant and diasporic people. The notion of home for diasporas has become an injured concept which forces them to face scars and fractures, blisters and sores, and psychic traumas on the move. In such a situation, unhomely home refers to the condition of living here and belonging elsewhere. Jhumpa Lahiritells the story of two generations of Indian family and their struggle to acculturate themselves in the west. She presents a gloomy spectacle of racism, prejudice and marginalization in which Gogol, the son of a Bengali couple, Ashoke and Ashima Ganguli, becomes a victim of it. Gogol struggles to transform himself by escaping from the traditions of the community of Indian immigrants to which his family belongs. He also cannot assimilate with the American culture. He is an ABCD, an American Born Confused Desi. Here, Lahiri depicts that the ABCDs are unable to answer the question: where are you from? This novel explores the inner psyche of characters and brings out stirring and teasing scene of identity by clash of cultures. This paper hypothesizes that neither the diasporas belong to the root nor to the foreign land. They belong to nowhere. This hypothesis is tasted with postcolonial diasporic criticism.